Socio-economic monitoring of fisher's conditions in selected sites of Guimaras affected by the 2006 oil spill - Subade, Rodelio F.; Jugado-Galero, Evelyn (2011)
On August 11, 206, M/T Solar 1 sank off the southern coast of the province of Guimaras, Philippines carrying with it some 2.2 million liters of bunker fuel. The oil leaked from the tanker and affected 194 km of coastline in the municipalities of Nueva Valencia, Sibunag, and San Lorenzo. The concomitant huge environmental impacts of the oil spill led to the temporary collapse or cessation of fishing in several villages during the first few months of the environmental disaster. In monitoring the recovery, restoration, and resiliency, of social and economic systems affected by the oil spill, it was vital to analyze major economic activities such as fishing. This study aimed to determine how fishers, after two years, recovered from the impact of the oil spill that affected Barangays La Paz and San Roque of Nueva Valencia municipality. A non-affected site, Brgy. Lawi in Jordan, Guimaras was selected to serve as a control site, Socio-economic survey was conducted to a total of 135 fisher-respondents. Key informant interviews and focused group discussions were also conducted. Results of the study showed that the oil spill had directly affected people in Guimaras who engaged in fishing, Results of the first and second yer socio-economic monitoring revealed that majority of the fishers in Brgys. Lapaz, San Roque and Lawi have resumed fishing, but fish catch two years after the oil spill did not improve significantly. Survey data revealed that monthly fishing income was subsistence in returns and was below the poverty threshold. In order to improve the socio-economic condition of fishers in Guimaras, recommendations were provided for national and local government units.
Keywords: Oil spills -- Guimaras; Oil spills -- Prevention; Oil spills and the environment